Analisis Tingkat Kesehatan KSPS BMT Rama Tahun 2010 Berdasarkan Metode CAMEL (Capital, Assets, Management, Efficiency, Liquidity) - Zulfa Saiban (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2011)
Health financial institution is institution that can keep their credibility in society perspective, government, and also their costumer. Health financial institution mean that those was hold operational and management based on regulation/law and manage profesional. Health level appraisal of institution is appraisal on institution/cooperation ability to holding operational activities based on regulation. Health level appraisal can used as a measurement for management to appraise their operational activities. Further more, health level appraisal can used to evaluate management and to determinite the direction of developing institution. Externally, health level appraisal can affect to loyality of the customer to their cooperation. Ordinary, health level appraisal do to financial institioun such as bank/BPR which based on the CAMEL, this analysys include capital, asset, management, efficiency, and likuidity. Especially to non-bank financial institution like cooperation add two component : growth and cooperation identity.